Detecção de inibidores de tripsina em genótipos de amendoim visando controle de pragas de grãos armazenados - Martins, Patrícia de Lima (2013)
Peanut (Arachis hypogaea L.) is an oilseed very expressive worldwide, due to commercial value of its oil. In Brazil, crop is grown in all regions, in order to attend in natura and food markets. The post-harvest is serious problem that affect the final output of the crop, which in inappropriate conditions, lead to occurrence of pests in stored grains. Some legumes contain protease inhibitors (PI) in their seeds that act directly in defense against grain pests, causing damage in nutrient absorption and further death. The objective of this study was to detect the presence of trypsin inhibitors in peanut genotypes and to study the potential inhibition against digestive enzymes in Alphitobius diaperinus and other agricultural pests. PI detection was carried out in 10 peanut genotypes belonging to Improvement Program at Embrapa Algodão (Campina Grande, PB, Brazil). Total proteins from seeds were extracted in each accession, quantified, fractionated with ammonium sulfate, and submitted thermal stability and pH tests, for further assays. All peanut genotypes showed PI in seed-protein extracts, however the highest inhibition rate for digestive enzymes of A. diaperinus was found in L7 BRS 151, which also reduced the number of larvae, in bioassay. The CNPA AM 280 showed the highest inhibition rate in both assays, bovine trypsin and intestinal homogenate of A. diaperinus. This genotype was also highly stable in different pH and temperature assays and inhibited the intestinal serine proteases from Spodoptera frugiperda, Tenebrio molitor and Tribolium castaneum, in 16%, 42% and 82% respectively. The results obtained in this study are quite relevant due to contribute with the reduction of grain losses in post-harvest, considering that genotypes investigated here have interesting traits for further use as genetic resources with resistance to pests.